Simulation of double spend attack on the “Proof of Work” consensus protocol - Полуяненко, Н.А.; Кузнецов, А.А. (Radiotekhnika, 2019)
A critical analysis of the well-known analytical estimates of the probability of successful implementation of a double-spending attack on the “Proof of work” consensus protocol has been carried out. In particular, the so-called “Player ruin problem” is considered, it is shown that the basic assumptions about the probability space (the set of elementary outcomes and the likelihood of their occurrence) do not correspond to the real processes that occur when the “Proof of work” consensus is established in the blockchain system. A model of “independent players” is proposed, which eliminates the main inaccuracies and inconsistencies. The convergence of the results of theoretical calculations with the data of experiments to simulate the "race" between honest players and attackers is shown.